2021
DOI: 10.3390/vaccines9091047
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies against SARS-CoV-2, Anti-Ad5 Antibodies, and Reactogenicity in Response to Ad5-nCoV (CanSino Biologics) Vaccine in Individuals with and without Prior SARS-CoV-2

Abstract: This is the first study outside of clinical trials (phase I–III) evaluating the ability of the Ad5-nCoV vaccine to generate neutralizing antibodies and the factors associated with optimal or suboptimal response. In a longitudinal assay, 346 people (117 with prior COVID-19 and 229 without prior COVID-19) vaccinated with Ad5-nCoV were recruited. The percentage of neutralizing antibodies against SARS-CoV-2 (Surrogate Virus Neutralization Test) and antibodies against Ad5 (ADV-Ad5 IgG ELISA) were quantified pre and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 56 publications
4
26
1
Order By: Relevance
“…In Mexico, there are no reports on the seroprevalence of anti-Ad5 antibodies in the general population; however, a study reported that around 23% of cases associated with acute respiratory infections in children were related to adenovirus [ 25 ]. In addition to this, in our previous study [ 11 ], we reported a slight increase in the presence of anti-Ad5 antibodies after vaccination with Ad5-now. All this suggests that a detailed analysis should be carried out to examine whether it is convenient to use a booster dose with the same vaccine for those who have received the Ade5-nCoV vaccine or whether, the heterologous vaccination scheme, using ChAdOx1 nCoV-19, for example could be most beneficial.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In Mexico, there are no reports on the seroprevalence of anti-Ad5 antibodies in the general population; however, a study reported that around 23% of cases associated with acute respiratory infections in children were related to adenovirus [ 25 ]. In addition to this, in our previous study [ 11 ], we reported a slight increase in the presence of anti-Ad5 antibodies after vaccination with Ad5-now. All this suggests that a detailed analysis should be carried out to examine whether it is convenient to use a booster dose with the same vaccine for those who have received the Ade5-nCoV vaccine or whether, the heterologous vaccination scheme, using ChAdOx1 nCoV-19, for example could be most beneficial.…”
Section: Discussionsupporting
confidence: 75%
“…From 28 April to 4 May 2021, the Mexican government performed a vaccination campaign against COVID-19 with the Ad5-nCoV vaccine for teachers from Jalisco, Mexico. On the last week of May 2021 (21–24 days after vaccination), some of those professors were invited to voluntarily participate in a study to evaluate reactogenicity to the Ad5-nCoV vaccine, the production of neutralizing antibodies against SARS-CoV-2, and the anti-Ad5 Antibodies in response to this vaccine [ 11 ]. Six months later, the previous study participants were again invited to assess a possible decline in neutralizing titers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A safety report published in March 2021 showed an efficacy of 76.0% from participants who received a single standard dose from day 22 to day 90 of vaccination, whereas in participants who received two standard doses, the efficacy was increased to 81.3% ( Voysey et al, 2021 ). The CanSino AD5-nCOV vaccine is given by intramuscular injection, aerosol inhalation, or both and has been shown to induce higher nAbs percentage in individuals with history of COVID-19 infection than those without prior COVID-19 infection ( Hernández-Bello et al, 2021 ). Aerosolised Ad5-nCoV is well received, although two doses of aerosolised AD5-nCoV elicited similar nAb responses to one dose of intramuscular injection ( Wu et al, 2021 ).…”
Section: The Other Covid-19 Vaccinesmentioning
confidence: 99%
“…The use of SARS-CoV-2 reference strains or clinical isolates for NAb titration experiments requires Biosafety Level 3 (BSL-3) laboratories, which are scarce in Latin America. As a result, few reports are available about SARS-CoV-2 NAb in the Mexican population, with all currently available data relying on a neutralization-surrogate ELISA kit 1517 . During a pandemic, access to specific research reagents, such as an imported ELISA kit, is limited which cause long delays to the evaluation of the effectiveness of the national vaccination program and to the monitoring of the seroprevalence of the disease, both important aspects in the control of COVID-19.…”
Section: Introductionmentioning
confidence: 99%